Comparison of antimicrobial activity of sodium hypochlorite 2.5%, iodide potassium iodide 2%, and chlorhexidine 2% on the enterococcus faecalis after root canal filling - Fatemeh Mokhtari; Amir Hossein Mansor Abadi; Ali Gharaati Jahromi; Ehsan Anvar; Zandi Hengame; Tabrizi zade Mehdi; Taghavi Mayam (Tehran University of Medical Sciences, 2015)
Background and Aims: Bacteria and their products have a major role in pulp and periapical diseases. The purpose of this study was to compare the antimicrobial activity of sodium hypochlorite, iodide potassium iodide and chlorhexidine on the enterococcus faecalis after root canal filling. Materials and Methods: In this experimental study, 95 single canal human teeth were collected. Then after washing and cleaning and filing, the sterilization done using an autoclave. The teeth were smeared with enterococcus faecalis except five which selected as controls and then divided them into 3 groups which A randomly represented the irrigation by sodium hypochlorite, iodide potassium iodide (IKI) and chlorhexidine solution were done. The teeth were filled with gutta-percha and then incubated in a incubator for 90 days at a temperature of 37° C. The specimens were analyzed for Colony Count. Data were analyzed using Kruskal-Wallis test and Chi-Square. Results: According to the results of this study, the correlation between the 3 groups of cultured teeth were not significant (P=0.812).The specimens which were washed by IKI had the most positive amount of cultures (23.3%) and the specimens which washed by chlorhexidine had the lowest (16.7%). Conclusion: The results of this study showed that after the use of different wash solutions, no statistically significant difference exist in their antimicrobial activity after root canal therapy.